IMPLEMENTASI PENDIDIKAN KARAKTER PADA LAYANAN BIMBINGAN DAN KONSELING - Hartono, Hartono (LPPM Universitas PGRI Adi Buana Surabaya, 2011)
Character education is an important tool in the formation of student character. In practical guidance and counseling services in the schooling setting, character education is implemented through two ways, first directly through the services of guidance and counseling provided to students/counselees, which are grouped into four components: (1) the component of basic service, (2) the component of responsive service, (3) the component of individual planning service, and (4) the components of the system support service. Loads of character education materials written in guidance and counseling services that include the areas of personal guidance, social guidance, learning guidance, career guidance, and character development. Second, indirectly, by example attitude and behavior of guidance and counseling teachers/counselors along with the cultivation of creative cultural, innovative, productive, collaborative, discipline, sense of belonging, and responsibility.